2021
DOI: 10.1094/pbiomes-08-19-0045-r
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plant Host and Organ, Management Strategy, and Spore Traits on Microbiome Composition

Abstract: Microbiomes from maize and soybean were characterized in a long-term three-crop rotation research site, under four different land management strategies, to begin unraveling the effects of common farming practices on microbial communities. The fungal and bacterial communities of leaves, stems, and roots in host species were characterized across the growing season using amplicon sequencing and compared with the results of a similar study on wheat. Communities differed across hosts, and among plant growth stages … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 101 publications
2
7
0
Order By: Relevance
“…A higher proportion of fOTUs altered by fungicide application in the no-till management system showed improved resilience within the study period, which may be explained by the differences in microbial communities present in the phyllosphere of each management before fungicide applications, as has been demonstrated previously at the KBS LTER site (Longley et al, 2020;Gdanetz & Trail, 2017). A previous study from the KBS LTER site has demonstrated that aerially dispersed yeasts are enriched in the phyllosphere but also found in lower abundance in belowground plant organs (Gdanetz et al, 2021).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A higher proportion of fOTUs altered by fungicide application in the no-till management system showed improved resilience within the study period, which may be explained by the differences in microbial communities present in the phyllosphere of each management before fungicide applications, as has been demonstrated previously at the KBS LTER site (Longley et al, 2020;Gdanetz & Trail, 2017). A previous study from the KBS LTER site has demonstrated that aerially dispersed yeasts are enriched in the phyllosphere but also found in lower abundance in belowground plant organs (Gdanetz et al, 2021).…”
Section: Discussionsupporting
confidence: 66%
“…CC-BY-NC-ND 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is madeThe copyright holder for this preprint this version posted September 21, 2021. ; https://doi.org/10.1101/2021…”
mentioning
confidence: 99%
“…Sampling and DNA extractions were performed as described previously [37,42]. In addition, amplicon sequencing library preparation, bioinformatic sequence processing, and preprocessing before statistical analyses were performed as previously described [37,43,44].…”
Section: Sample Collectionmentioning
confidence: 99%
“…Temporal development of fungal communities in root and shoot tissue has not yet been reported in detail yet although several studies show clear differences in roots vs shoots communities at certain growth stages of crop development [11,26]. The type of habitat in leaves, stems and heads determines community structures, and fungal members that have specialized habitat preferences depending on growth habits [42], for instance, Epicoccum and Alternaria evolved to colonize certain tissues [43].…”
Section: Discussionmentioning
confidence: 99%